Advances in Mechatronics and Control Engineering III Selected, peer reviewed papers from the 2014 3rd International Conference on Mechatronics and Control Engineering (ICMCE 2014), August 27-28, 2014, Zhuhai, China (Trans Tech Publications Ltd, 2014)
Collection of selected, peer reviewed papers from the 2014 3rd International Conference on Mechatronics and Control Engineering (ICMCE 2014), August 27-28, 2014, Zhuhai, China. Volume is indexed by Thomson Reuters CPCI-S (WoS).The 135 papers are grouped as follows: Chapter 1: Artificial Intelligence, Algorithms and Computation Methods; Chapter 2: Mathematical Methods and Data Mining, Information Technologies in Industry;Chapter 3: Sound, Image, Signal and Video Processing and Technologies; Chapter 4: Sensors, Testing, Detection, Instrumentation, Measurement and Monitoring Technologies; Chapter 5: Design Technologies in Mechatronics, Industrial Robots, Automation and Control Technologies; Chapter 6: Computer Networks, Communications Technology and E-Applications; Chapter 7: Modern Electronic, Power and Circuit Technologies, Electrical Systems; Chapter 8: Materials and Manufacturing Processes, Applied Mechanics; Chapter 9: Engineering Education, Engineering Management and Industrial Engineering Keyword: Artificial Intelligence, Algorithms and Computation Methods; Mathematical Methods and Data Mining, Information Technologies in Industry; Sound, Image, Signal and Video Processing and Technologies; Sensors, Testing, Detection, Instrumentation, Measurement and Monitoring Technologies; Design Technologies in Mechatronics, Industrial Robots, Automation and Control Technologies; Computer Networks, Communications Technology and E-Applications; Modern Electronic, Power and Circuit Technologies, Electrical Systems; Materials and Manufacturing Processes, Applied Mechanics; Engineering Education, Engineering Management and Industrial Engineering Containing 135 papers from the 2014 3rd International Conference on Mechatronics and Control Engineering (ICMCE 2014), held in August 2014 in Zhuhai, China, this volume presents research on mechanical engineering, electronic control, and systems thinking in the design of products and manufacturing processes. Papers address artificial intelligence, algorithms, and computation methods; mathematical methods and data mining and information technologies in industry; sound, image, and video processing and technologies; sensors, testing, detection, instrumentation, measurement, and monitoring technologies; design technologies in mechatronics, industrial robots, automation, and control technologies; computer networks, communications technology, and e-applications; modern electronic, power, and circuit technologies and electrical systems; materials and manufacturing processes and applied mechanics; and engineering education, engineering management, and industrial engineering. Contributors work in computer science, engineering, technology, and other areas, mainly in China. - Algorithms and data structures- Mathematics- Mechanical engineering- Research -- Instrumentation -- Measurement